Image cytometry of irregular microplastic particles in a cross-slot microchannel utilizing viscoelastic focusing - Kim, Bookun; Lee, Hwang; Lee, Seong Jae; Kwon, Jung-Hwan; Kim, Ju Min (The Korean journal of chemical engineering, 2020)
Microplastic particles have recently attracted much attention owing to their potential adverse effects on marine and terrestrial environments. Although several studies have been conducted on this topic, one of the prominent existing challenges is developing analytical methods to precisely characterize isolated microplastics. Specifically, a systematic method that determines both the size and shape of irregular micron-sized particles is required because conventional optical methods provide only two-dimensional images of microplastics and cannot easily handle cases of tilting or aggregation of particles. In this study, we demonstrate that previously developed microfluidic technologies can be successfully applied to measure the size and shape of oblate microparticles utilizing viscoelastic particle focusing. Furthermore, this technique is also applicable for irregular microplastic fragments that are predominantly found in environmental samples.